Comparison between Hydrodistillation with Steam Explosion and Conventional Hydrodistillation in Kaffir Lime Oil Extraction - Yustina Wuri Wulandari; Supriyadi Supriyadi; Chairil Anwar (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Steam explosion was proposed as a pretreatment method to accelerate the hydrodistillation (SE-HD) of kaffir lime leaves. This research aimed to compare SE-HD and conventional hydrodistillation (HD) in terms of extraction yield, extraction time, chemical composition, and essential oil quality. The extraction of kaffir lime oil with SE-HD was superior to HD with regard to extraction time (35 min. vs 120 min.) and extraction yield (1.386% vs 1.182%). The chemical composition and the quality of the extracted essential oil from both methods were quite similar, indicating the absence of adverse influence from the application of steam explosion as pretreatment. Therefore, SE-HD was a fast and an energy-saving method for extracting essential oil from kaffir lime leaves.